2011
DOI: 10.1002/hipo.20819
|View full text |Cite
|
Sign up to set email alerts
|

Rapid consolidation and the human hippocampus: Intracranial recordings confirm surface EEG

Abstract: ABSTRACT:Diverse studies demonstrated that although immediately repeated stimuli are better and faster recognized than stimuli repeated after a delay, this comes at the price of less-efficient long-term retention. A recent-evoked potential study using source estimation of high-resolution scalp EEG indicated that while immediate repetition induced a strikingly different electrical activity than new items in the left-medial temporal lobe (MTL) after 200-300 ms, delayed repetition did not. In this study, we recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 21 publications
1
49
3
Order By: Relevance
“…The present findings could benefit from the simultaneous recording of scalp EEG which could allow a useful comparison with existing literature on the same topic [24], [75]. This will be the focus of future studies including a larger set of patients.…”
Section: Discussionmentioning
confidence: 76%
“…The present findings could benefit from the simultaneous recording of scalp EEG which could allow a useful comparison with existing literature on the same topic [24], [75]. This will be the focus of future studies including a larger set of patients.…”
Section: Discussionmentioning
confidence: 76%
“…This technique is capable of localizing epileptic discharges emanating from the medial temporal lobe [68] and correctly localized MTL activity in healthy subjects performing a memory task [69], as confirmed by depth electrode recordings in epileptic patients performing the same task [70]. There is no theoretical reason to consider the OFC a less amenable region to this localization technique than the MTL, but formal proof is lacking.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies suggest that anterior temporal spikes recorded on the scalp are rather the result of anterior or lateral neocortical temporal activity or common activity of neocortical and mesial temporal sources, and that neither EEG nor MEG can see spikes confined to the mesial temporal structures (Alarcon et al , 1994; Emerson et al , 1995; Huppertz et al , 2001; Gavaret et al , 2004; Wennberg 2011). However, simultaneous surface and intracranial EEG studies indicated that deep mesial temporal sources could be properly localized by electric source imaging if their small volume-conducted signals can be identified in the scalp EEG, or if they are averaged (Lantz et al , 2001; Nayak et al , 2004; Zumsteg et al , 2005; Nahum et al , 2011). It remains to be shown in future studies using simultaneous intracranial EEG if mesial temporal interictal epileptiform discharges could be localized non-invasively with high-density EEG/MEG or with combined EEG–functional MRI (Sperli et al , 2006; Kaiboriboon et al , 2010; Vulliemoz et al , 2010; Grouiller et al , 2011).…”
Section: Discussionmentioning
confidence: 99%